A loucura na antropologia de Hegel - Saraiva, Guilherme José Sousa (2025)
In Anthropology, Hegel presents the process of dialectical development of the soul, inserting madness as a moment in the dialectical logic of the Spirit. In this research, we will seek to scrutinize the philosophical status Hegel establishes for madness, as well as its systematic position in the dialectical structure of subjectivity in Anthropology. Anthropology consists of the process of dialectical development from the natural soul to the effective soul, where the feeling soul is the intermediate moment in which the internal split occurs, which will then be subsumed in the mediated structure of rational consciousness. Madness functions as a regression of rational consciousness into an abyss of undifferentiation. Due to this deviation from rational consciousness, madness is the experience of dialectics (negation and negation of negation) without mediation; while madness is an immediate negativity, rational consciousness is a mediated negativity. Madness, as a dialectical figure, is a daydream, an immediate concrete abstraction, which is the result of the regression of rational consciousness into a moment of indeterminacy. The excess negativity in madness thus provokes a projection and replacement of reality by the unconscious dream life, functioning as a night of reason. In this sense, madness is a pathology of the soul as a rupture of connections with objective reality and a regression of rational consciousness through an excess of unmediated negativity. Desire, in madness, is within the realm of a nostalgia that fantasizes about a paradisiacal and harmonious unity that was lost and which one seeks to rediscover. The effective soul, as rational consciousness and actuality of the spirit, corresponds to a mediated structure; habit, which is defined as second nature, is the subsumed and self-differentiated natural soul. Habit, as a mediated activity of rational consciousness, constitutes the prerequisite for the treatment of madness. Since madness is immanent to reason, it assumes an ontological moment, as a possibility, in the negative dialectical structure of the subject. In this sense, this dissertation investigated the functioning of madness based on Hegel's Anthropology, which is located in the first section of the Subjective Spirit, in the third volume of the Encyclopedia of Philosophical Sciences (2011), the Philosophy of Spirit.